Efficacy of Over-the-Scope Clips Compared to Standard Therapy for Nonvariceal Upper Gastrointestinal Bleeding—A Systematic Review and Meta-analysis of Randomized Trials - Giri, Suprabhat; Harindranath, Sidharth; Kozyk, Marko; Kale, Aditya; Jearth, Vaneet; Sundaram, Sridhar (Journal of Digestive Endoscopy, 2023)
The current standard of treatment for nonvariceal upper gastrointestinal bleeding (NVUGIB) includes endoscopic hemostasis with either through-the-scope clips or thermal therapy. However, they may be associated with rebleeding, especially in high-risk ulcers. Over-the-scope clips (OTSC) have been demonstrated in multiple recent studies to be an effective measure for NVUGIB. We aimed to analyze the current literature on standard therapy with OTSC to manage NVUGIB. A meta-analysis was performed by pooling the data from randomized studies obtained from a comprehensive search of Medline, Embase, and Scopus from inception to February 2023. The outcomes analyzed included rates of persistent bleeding, rebleeding, mortality, and duration of hospitalization. A total of five studies were included in the final analysis. There was no significant difference in the risk of persistent bleeding between the groups, with a risk ratio (RR) of 0.29 (95% confidence interval [CI]: 0.07–1.27). The use of OTSC was associated with a significantly lower risk of 7-day and 30-day rebleeding compared with standard therapy with RR of 0.30 (95% CI: 0.16–0.59) and 0.42 (95% CI: 0.24–0.72), respectively. There was no difference in the risk of 30-day mortality or the duration of hospitalization. There was no change in the effect on subgroup analysis of studies using OTSC as first-line therapy. The use of OTSC can reduce the rebleeding rates after endoscopic hemostasis. However, they may not reduce the risk of persistent bleeding or mortality. Future studies are required on the cost-efficacy of this modality.
Keywords: upper gastrointestinal bleeding; peptic ulcer bleeding; over-the-scope clips; through-the scope clips; meta-analysis